MENINGKATKAN KARAKTER ISLAMI SISWA MELALUI PROGRAM TAHFIDZ QUR’AN DI LEMBAGA PENDIDIKAN - Sri Nurhayati; Iwan Hermawan; Nur Aini Farida (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This research is to find out the methods or models applied in schools to improve students' Islamic character through the tahfidz Qur'an program. The method used is a method with literature studies or literature studies. Where data sources are obtained through journals, books or articles. In the framework of forming the Islamic character of students, educational institutions are considered to have an important role in achieving this. One of the efforts to form an Islamic character is by tahfidz Qur'an education. Forming Islamic character through tahfidz qur'an education can be done with various applied models including: 1) command model (al-amr) 2) prohibition model 3) motivational model (targib) 4) tarhib model 5) dialogue and debate model 6) habituation model.Â Kata Kunci: Character Building; Tahfidz, Qur'an